Comparação de dois Protocolos de sedação em Bugio - Ruivo (Alouatta Guariba Clamitans) - Natália Fagundes (2018)
The howler monkey (Alouatta Guariba Clamitans) is one of the most common primates species found in the south of Brazil. Nowadays, the rescue centers and fauna maintainers are in a situation of superpopulation, therefore methods of population control that does not discharacterize the species natural behavior, like the vasectomy. The aim of this study was to evaluate and compare cardiorespiratory and hemogasometric parameters, as well as quality of sedation, time and recovery of two protocols with the following estimated doses: ketamine (10 mg.kg-1) or dexmedetomidine (10 g.kg-1) associated with midazolam 0.5 mg.kg-1) and butorphanol (0.3 mg.kg-1) administered intramuscularly (CBM and DBM, respectively). Twelve howler monkeys were randomly selected in 2 groups (n = 6 per group) and evaluated for the parameters HR, RR, SAP, DAP, MAP, SpO2, EtCO2, RT and sedation scale, from 5 minutes after the latency period up to 30 minutes after latency. Arterial blood gas and lactate were also collected at 5 and 30 minutes. And also the duration of sedation and time to recovery. ANOVA followed by paired t-test (parametric) and Mann Whitney Rank Sum Test (non-parametric) with p <0.05 were performed. There was no difference between protocols in the latency time being DBM 7.6 ± 1.6 min and CBM 5.83 ± 1.6 min. The heart rate in the DBM group was significantly lower at all times (on average 34% lower). RR, SpO2, arterial lactate, blood pressure and temperature decreased over time. Hemogasometric parameters did not differ between groups or over the observed time. The total sedation score was greater at times 5, 10 and 15 minutes in the DBM group. Recovery time in the dexmedetomine group was significantly faster in relation to ketamine (25.6 ± 9 min). All animals had moderate hypoxemia (PaO2 <70 mmHg). It is concluded that both protocols produce satisfactory sedation and analgesia, but dexmedetomidine provides deeper sedation with faster recovery, with lower heart rate. Both protocols presented moderate hypoxemia, supplementation of oxygen is recommended when they are used.